2015
DOI: 10.1007/s11085-015-9570-3
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation Resistance of Thermal Barrier Coatings Based on Hollow Alumina Particles

Abstract: Thermal barrier coatings were synthesized in a single step process from a slurry containing Al microspheres onto different Ni-based superalloys. Upon growth of the coating a top coat of hollow alumina spheres linked to an aluminium diffused coating through an alumina TGO formed. The isothermal and cyclic oxidation tests at different temperatures (900 till 1100°C) up to 1000 h or 1500 cycles revealed progressive growth of different thermal oxides depending on the substrate composition. Faster degradation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Therefore, they cannot be applied to other sections that now require thermal insulation due to the increase of the turbine inlet temperatures. Among the alternative coating techniques, slurries containing Al microspheres appear particularly attractive as they can form a top foam of hollow alumina microspheres in addition to an aluminide coating [1][2][3][4][5]. It has been demonstrated that just a 40 µm -thick top foam indeed confers thermal insulation equivalent to those of 400 µm thick conventional plasma-sprayed coatings made of yttria-stabilized zirconia between 400°C and 900°C [6].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, they cannot be applied to other sections that now require thermal insulation due to the increase of the turbine inlet temperatures. Among the alternative coating techniques, slurries containing Al microspheres appear particularly attractive as they can form a top foam of hollow alumina microspheres in addition to an aluminide coating [1][2][3][4][5]. It has been demonstrated that just a 40 µm -thick top foam indeed confers thermal insulation equivalent to those of 400 µm thick conventional plasma-sprayed coatings made of yttria-stabilized zirconia between 400°C and 900°C [6].…”
Section: Introductionmentioning
confidence: 99%
“…The diffusional processes taking place in the coatings under exposure to the temperatures applied in the present study can be explained based on the results of the work by Pedraza et al [ 31 ], who investigated both the isothermal and cyclic oxidation of aluminum-rich coatings. The current paper is complementary to [ 31 ] because it focuses on the very top near outer layer of the coating.…”
Section: Resultsmentioning
confidence: 99%
“…The diffusional processes taking place in the coatings under exposure to the temperatures applied in the present study can be explained based on the results of the work by Pedraza et al [ 31 ], who investigated both the isothermal and cyclic oxidation of aluminum-rich coatings. The current paper is complementary to [ 31 ] because it focuses on the very top near outer layer of the coating. The current paper demonstrates that with the exception of the formation of the alumina layer, all other occurring processes such as coarsening of the microstructure of the coatings, formation of pores, outward diffusion of Fe and Cr to the surface, degrade the insulation and protective properties of the heat-resistant coatings.…”
Section: Resultsmentioning
confidence: 99%